(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Reed (Phragmites australis) is a wetland- and waterside-grown plant species, which has been utilized in multifold ways during human life over centuries. This paper provides an overview of the use of reed as an edible material, medicinal uses, uses in daily life, uses in livestock farming, and uses as a source of renewable energy. Results of the study find out that reed is an environmentally friendly multi-purpose resource, and so opens up new horizons in the economic and health sectors as well.